Development of English Learning Module to Improve Student Critical Thinking Ability at The Faculty of Law University of Prof. Dr Hazairin, S.H.: English Learning Module - Yosi Marita; Siti Masitah; Friang Br. Haloho (English Education Study Program Faculty of Teacher Training and Education, 2022)
The academic world requires English language skills to lead students to understand science that continues to develop to improve quality human resources in facing globalization competition. English proficiency is one of the places for developing human resource evaluations that must be managed interactively and professionally. English proficiency is one of the places for developing human resource evaluations that must be managed interactively and professionally. Learning and modules are two things that complement each other. Learning will take place effectively equipped with learning media. Therefore, it is very necessary to produce a product of teaching materials in the form of modules that are not only intellectual but also can create students to be more creative and innovative. The development of learning modules used ADDIE development. ADDIE has a five-stage model development among others : Analyze (Analyze), Design (Design), Develop (Develop), Implement (Apply), and Evaluate (Evaluate). The assessment of learning modules for material experts was divided into 4 aspects. The results of the assessment of each aspect showed the different average score. In the Feasibility of contents, the average score was 3.7, it means it was